Media Political Communication: Textual Analysis Of News Coverage On The Development Of Mining Areas In Raja Ampat (Coverage On Tempo Online And Media Indonesia) - Afina Ruqayyah (Jurnal Komunikasi, Masyarakat dan Keamanan, 2025)
ABSTRACT In his book "Mass Communication Theory", Denis McQuail explains that the emergence of internet technology has brought the spectrum of mass media into a new force of communication, influencing social integration, disintegration, and public enlightenment through information disseminated by mass media. Mass media cannot be separated from its role as a medium for advertising, entertainment, and as a tool for economic and political propaganda to influence public opinion on various issues. The issue of nickel mining activities in the Raja Ampat region in 2025, for example, was reported with different tones by Tempo and Media Indonesia. Tempo, known for its investigative journalism style and founded by liberal-minded figure Goenawan Mohamad, tends to portray the nickel mining issue with a negative sentiment. In contrast, Media Indonesia, owned by Surya Paloh and closely affiliated with the government, tends to frame the issue more positively. These differences in reporting perspectives align with the framework of media and society formation theory (Westley & MacLean, 1957, in McQuail, 2010), which highlights the key determinants of media coverage, such as institutional control, organizational motives, involvement of other social institutions, and the portrayal of reality shaped by each institution’s “media logic. Keywords : Mass Media; Nickel Mining; Raja Ampat; Media Political Economy; Media and Society Formation Theory